Prostitution bag sløret - Persson, Nahid (Sweden : Hogel, Jacob, 2005)
Nahid Persson returns to Iran after living for 17 years in emigration in Sweden. Coming back as a documentary filmmaker, she originally intends to make a film about an elderly man, Habib, who sells prophecies on the streets. But when she visits his run-down house, she is shocked and intrigued to discover that he shares it with Minna and Fariba, two heroin addicts who prostitute themselves to make a living and support their little children while both of their husbands are in prison. The women are neighbours, good friends and support each other. The film sympathetically explores their everyday life and the way prostitution functions in a country where adultery is persecuted, sometimes resulting in capital punishment. For men, there is a 'legal' way to buy sex and still comply with Muslim law: they marry the women in what is called 'Sighe', a temporary marriage legal in Shia Islam. 'Sighe' can last from two hours up to 99 years. In the film both Minna and Fariba undergo 'Sighe' with customers and Fariba gets married Sighe-style to Habib for 6 months. The film follows the women for more than a year, providing a personal and intimate look into the two tragic lives behind the veils.
Duration: 00:58:00
Keywords: Documentary films